2018
DOI: 10.1029/2018gl077212
|View full text |Cite
|
Sign up to set email alerts
|

Electron Scattering by Plasmaspheric Hiss in a Nightside Plume

Abstract: Plasmaspheric hiss is known to play an important role in radiation belt electron dynamics in high plasma density regions. We present observations of two crossings of a plasmaspheric plume by the Van Allen Probes on 26 December 2012, which occurred unusually at the post‐midnight‐to‐dawn sector between L ~ 4–6 during a geomagnetically quiet period. This plume exhibited pronounced electron densities higher than those of the average plume level. Moderate hiss emissions accompanied the two plume crossings with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…Plasmaspheric plumes are found to be favorable for enhancing pitch angle scattering of radiation belt electrons, thus leading to electron precipitation into the upper atmosphere (Borovsky et al, 2014;Summers et al, 2008;Zhang et al, 2018). Borovsky and Steinberg (2006) found that relativistic electron dropouts at geosynchronous orbit often coincided with the presence of plasmaspheric plumes, suggesting the potential loss of energetic electrons due to interactions with the enhanced plasma waves in plumes.…”
Section: 1029/2019gl082095mentioning
confidence: 99%
“…Plasmaspheric plumes are found to be favorable for enhancing pitch angle scattering of radiation belt electrons, thus leading to electron precipitation into the upper atmosphere (Borovsky et al, 2014;Summers et al, 2008;Zhang et al, 2018). Borovsky and Steinberg (2006) found that relativistic electron dropouts at geosynchronous orbit often coincided with the presence of plasmaspheric plumes, suggesting the potential loss of energetic electrons due to interactions with the enhanced plasma waves in plumes.…”
Section: 1029/2019gl082095mentioning
confidence: 99%
“…We further assume that the initial electron PSD follows a sinusoidal function of equatorial pitch angle. We define the electron loss timescale ( τ D ) as the exponential decay timescale after the approach of electron equilibrium state and then follow the studies of Ni et al () and Zhang et al () to calculate τ D as τD=tn+1tnitalicIn[]jn+1()αeqitalicIn[]jn()αeq. …”
Section: Electron Scattering Effect Of Plume Hissmentioning
confidence: 99%
“…Radiation belt electrons can be affected by various magnetospheric wave modes, including whistler mode chorus, plasmaspheric hiss, magnetosonic waves, electromagnetic ion cyclotron waves, and electrostatic electron cyclotron harmonic waves, via wave-particle interaction processes (e.g., Ni et al, 2016;Shprits et al, 2008;Summers et al, 2007;Thorne, 2010), and ultralow frequency wave-driven diffusion (e.g., Su, Zhu, Xiao, Zong, et al, 2015). Among these waves, hiss is typically regarded as a structureless, broadband whistler mode emission naturally occurring inside the plasmasphere (e.g., Meredith et al, 2004;Thorne et al, 1973), high-density plasmaspheric plumes (e.g., Summers et al, 2008;Zhang et al, 2018), and lowdensity plasmatrough (Hua et al, 2018;Su et al, 2018a;Zhu et al, 2015). A few recent studies reported hiss emissions with short-time (tens of milliseconds) rising and falling tones (Summers et al, 2014), long-lasting (~1 s) rising tones, and large amplitude (up to 1.5 nT) hiss waveforms in the plasmaspheric plumes (Su et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Circulation models cannot be applied for such small regions of space. Recent works on hiss within plumes (Hartley et al, 2019;Li et al, 2019;Nakamura et al, 2018;Shi et al, 2019;Teng et al, 2019;Zhang et al, 2018), although not the main focus of this paper, will be commented on in sections 4 and 5 of this paper in this light.…”
Section: Introductionmentioning
confidence: 99%